The Use of Molecular Diagnostics to Infer Migration Directions of Willow Warblers in the Southeast Baltic - Gürsoy Ergen, A.G.; Chernetsov, N.; Lundberg, M.; Äkesson, S.; Bensch, S. (Springer Verlag, 2017)
The Willow Warbler (Phylloscopus trochilus, Linnaeus, 1758) is a long distance migrant and one of the most common breeding birds in the Western Palearctic. Its migratory directions have been studied in detail in Scandinavia where a narrow migratory divide is located around 62°30′ N that separates southern SW migrating Phylloscopus t. trochilus from SSE migrating Phylloscopus t. acredula. The shape and location of the migratory divide in the countries south and east of the Baltic Sea is less well understood. In this study we explored the geographic origin and migratory phenotype of the Willow Warbler during breeding and migration at Rybachy, Kaliningrad, Russia. The sampling was divided into three periods: breeding (1–9 July), early autumn migration (25–31 August), and late autumn migration (1–17 September). The birds were genotyped at two bi-allelic loci (AFLP-WW1 and AFLP-WW2) and the results were compared to genotypes from several reference breeding populations from around the Baltic Sea. Samples from the breeding and early migration periods were dominated by genotypes associated with SW-migrating trochilus. However, several intermediate genotypes were also present among breeding birds suggesting that this area overlaps the hybrid zone extending from territories south of the Baltic Sea. During late migration, birds carried genotypes that are common among north Scandinavian Willow Warblers that apparently pass Rybachy on their migration SSE to wintering areas in tropical East and South Africa. © 2017, Dt. Ornithologen-Gesellschaft e.V.
Keywords: AFLP; Avian Migration; Migratory Direction; Migratory Divide; Phylloscopus Trochilus